(untitled) (The Conference Hub, 2025)
The article examines the use of art therapy (theatre) in preschool age. The author describes the stages of its production and the importance of theatre for the development of preschoolers. The researcher notes that theatre is a healing co-creation of children and adults, which contributes to a bright and interesting life not only in kindergarten, but also in society, developing in pupils their creative potential and harmonious relationships with the world.